HUBUNGAN TEMPAT PERINDUKAN NYAMUK ANOPHELES SUNDAICUS DENGAN KEJADIAN MALARIA DI KABUPATEN PASAMAN BARAT - sari, Mila (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Malaria is infectious disease caused of parasite plasmodium contangious though bitemosquito of Anopheles which infection. This disease can attacked everybody ofbaby, adult and also children. Regency West Pasaman occurrence to improvemalaria that is 87 malaria case. This research type is describtive with of crosssectional that is describt relationship breeding place mosquito of anophelessundaicus. Occurrence of malaria in Sikabau village regency of West Pasaman.Population counted 38 lead family and the samples get rit with simple randomsampling counted 68 lead family. Collecting data conducted by inspection andobservasion, processed data computerilized with analysis of univariate andbivariate. This research conducted February. Result analysis of univariate found bypresentase responden suffering from malaria 60,3%, there is breeding place 44,1%.From result of bivariate got by breeding place of mosquito of Anopheles sundaicushave relationship with occurrence of malaria (p≤0,005). Result of research can beconcluded that occurrence malaria in Sikabau Village Regency West Pasaman caninfluence by breeding place of anopheles sundaicus. Expected society to improvesanitation environment,with under breeding palce of mosquito Anopheles sundaicus.Key Word : Breeding Place, anopheles, malaria